Supplier Development at Astra Zeneca, China: Streamlining the Clinical Supply Chain through improved supplier capabilities - Bhardwaj, Saurabh (2011)
The development of a pharmaceutical product, on average, takes about 12 – 15 years and is rife with its unique set of challenges. Study Management, which is a rather important function in the R & D process, deals with setting up and completing clinical trials in a timely and cost effective manner. The clinical supply chain (C- Chain) which is just one of its constituent elements shall be our area of focus.